Proses Afiksasi Pada Surah Al- Ma'arij - Mukhtar. I. Miolo; Nur Fauzia Laubaha; Fauzia Ali (STIQ Amuntai, 2025)
Arabic as the language of the Qur'an has a complex morphological structure, one of which is through the process of affixation. Affixation includes the addition of prefixes, infixes, and suffixes that contribute to forming new meanings and enriching Arabic vocabulary. Surah Al-Ma'arij is chosen as the research object because it contains many interesting forms of affixation to be studied further. This research uses qualitative approach with library research method. The data is collected through the study of verses in Surah Al-Ma'arij as well as relevant literature that discusses affixation in Arabic.The results show that affixation in Surah Al-Ma'arij includes three types of affixes, namely prefixes, infixes, and suffixes. Prefixes found include the letters م (mim), ت (ta), ي (ya), and ن (nun) which are added at the beginning of the word to form a new meaning. Infixes are the letters alif, waw, and tasydid which are inserted in the middle of the base word. Meanwhile, suffixes in the form of additional letters و (waw), ن (nun), and ي (ya) are found at the end of words as grammatical markers. This affixation process enriches the word structure and clarifies the grammatical function in the context of the verse. The affixation in Surah Al-Ma'arij shows the complexity of Arabic morphology that allows the formation of variations in the meaning and function of words. An in-depth understanding of the affixation process is very important in interpreting the Qur'anic text more accurately. This research is expected to be a reference for Arabic linguistics and Qur'anic morphology studies in the future.